An Analysis of ‘the Law’: Legal Positivism - Howe, Tay Choon (Journal of Malaysian and Comparative Law, 2018)
The study of law is not just confined to accepting the rules as they are and applying them to factual circumstances. This article attempts to bring some contrast to the various legal theories from a legal positivism perspective in exploring, in broad terms, the justification for obedience to the law and whether such obedience is justified. One of the ever-pervading issues revolves around the interpretation and reception of what constitutes ‘(im)moral’ and ‘justice’. In this article, how the ‘law’ views ‘(im)morality’ and ‘justice’ is examined in the light of Nazi Germany during World War II vis-à-vis legal positivism. Whilst it is never meant be a treatise, it is hoped that by examining the legal theories and eminent jurists alike here, there will be some clearer understanding of what is understood to be the ‘law’.